To find the distance between the points B (-2, -6) and C (10, -1), we can use the distance formula:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Here, \((x_1, y_1)\) are the coordinates of point B, and \((x_2, y_2)\) are the coordinates of point C. Thus, we have:
\[ (x_1, y_1) = (-2, -6) \] \[ (x_2, y_2) = (10, -1) \]
Now, we can substitute these values into the distance formula:
\[ d = \sqrt{(10 - (-2))^2 + (-1 - (-6))^2} \]
Calculating the differences:
\[ 10 - (-2) = 10 + 2 = 12 \] \[ -1 - (-6) = -1 + 6 = 5 \]
Now plug these values back into the formula:
\[ d = \sqrt{(12)^2 + (5)^2} \] \[ d = \sqrt{144 + 25} \] \[ d = \sqrt{169} \] \[ d = 13 \]
Thus, the distance between points B and C is \( \boxed{13} \).